![image](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7Bx%5E2%7D%2B%5Cfrac%7B1%7D%7B%28x%2B2%29%5E2%7D%3D%5Cfrac%7B10%7D%7B9%7D%3B%5C%5C%0AD%28f%29%3Ax%5Cneq0%5Cbigcup+x%5Cneq-2%3D%3D%3Ex%5Cin%5Cleft%28-%5Cinfty%3B-2%5Cright%29%5Cbigcup%5Cleft%28-2%3B0%5Cright%29%5Cbigcup%5Cleft%280%3B%2B%5Cinfty%5Cright%29%3B%5C%5C%0A%5Cfrac%7B1%7D%7Bx%5E2%7D%2B%5Cfrac%7B1%7D%7B%28x%2B2%29%5E2%7D-%5Cfrac%7B10%7D%7B9%7D%3D0%3B%5C%5C%0A%5Cfrac%7B9%28x%2B2%29%5E2%2B9x%5E2-10x%5E2%28x%2B2%29%5E2%7D%7B9x%5E2%28x%2B2%29%5E2%7D%3D0%3B%5C%5C%0A9%28x%2B2%29%5E2%2B9x%5E2-10x%5E2%28x%2B2%29%5E2%3D0%3B%5C%5C%0A9%28x%5E2%2B4x%2B4%29%2B9x%5E2-10x%5E4-40x%5E3-40x%5E2%3D0%3B%5C%5C%0A-10x%5E4-40x%5E3-40x%5E2%2B18x%5E2%2B36x%2B36%3D0%3B%5C%5C%0A10x%5E4%2B40x%5E3%2B22x%5E2-36x-36%3D0%3B%5C%5C%0Ax%3D1%3A10%2B40%2B22-36-36%3D72-72%3D0%3B%5C%5C%0A)
x\in\left(-\infty;-2\right)\bigcup\left(-2;0\right)\bigcup\left(0;+\infty\right);\\
\frac{1}{x^2}+\frac{1}{(x+2)^2}-\frac{10}{9}=0;\\
\frac{9(x+2)^2+9x^2-10x^2(x+2)^2}{9x^2(x+2)^2}=0;\\
9(x+2)^2+9x^2-10x^2(x+2)^2=0;\\
9(x^2+4x+4)+9x^2-10x^4-40x^3-40x^2=0;\\
-10x^4-40x^3-40x^2+18x^2+36x+36=0;\\
10x^4+40x^3+22x^2-36x-36=0;\\
x=1:10+40+22-36-36=72-72=0;\\
" alt="\frac{1}{x^2}+\frac{1}{(x+2)^2}=\frac{10}{9};\\
D(f):x\neq0\bigcup x\neq-2==>x\in\left(-\infty;-2\right)\bigcup\left(-2;0\right)\bigcup\left(0;+\infty\right);\\
\frac{1}{x^2}+\frac{1}{(x+2)^2}-\frac{10}{9}=0;\\
\frac{9(x+2)^2+9x^2-10x^2(x+2)^2}{9x^2(x+2)^2}=0;\\
9(x+2)^2+9x^2-10x^2(x+2)^2=0;\\
9(x^2+4x+4)+9x^2-10x^4-40x^3-40x^2=0;\\
-10x^4-40x^3-40x^2+18x^2+36x+36=0;\\
10x^4+40x^3+22x^2-36x-36=0;\\
x=1:10+40+22-36-36=72-72=0;\\
" align="absmiddle" class="latex-formula">
значит имеем лишь 2 корня
х=1 и х=-3проверим решения